Role of IL6 antagonist, tocilizumab in treating Covid 19; a systematic review - Al-Ameri, Ali Mansoor (Karbala Journal of Medicine, 2021)
Background and objective: Coronavirus disease 2019 (Covid 19) is the most severe pandemic hitted the world during the last century. Generally, the diseases course has two phases, a viral phases and a more damaging immune mediated phases. The latter might leed to major organ failure and even death. Many therapeutic options has been tried most of them have not proven regarding safety and efficacy. Tocilizumab is the most Widely used cytokine antagonist in order to combat fo the cytokine storm of covid 19. It is an Anti- IL 6 monoclonal antibody used in severe cases to reverse the expected cytokine storm. Until recently, there is insufficient data regarding indications, safety, efficacy and exact dosing regimen of tocilizumab. The current systematic review tried to answer the above parameters in question. Method: This is a systematic review involving the effectiveness, dose and indications of tocilizumab as a treatment option for covid 19 infection. To do so, search on Pubmed using the following passwords: tocilizumab, covid 19, effectiveness, dose and indication with varying mixes. Results: the search results revealed a total of 514 results, of them only 236 were included in this review. Conclusion: Tocilizumab, is highly effective therapy especially for severe and critical covid 19 infections. The usual recommended dose by FDA (upto 3 infusions of 8 mg/ kg body wt.) is the rule, but can be udsed in a lower dosage and as a single dose, also.